2014
DOI: 10.1016/j.lungcan.2014.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Activation of AMP-activated protein kinase sensitizes lung cancer cells and H1299 xenografts to erlotinib

Abstract: OBJECTIVES: The therapeutic scheme for non-small cell lung cancer (NSCLC) patients can be improved if adapted to the individual response. For example, 60-70% of adenocarcinoma patients show response to EGFR-tyrosine kinase inhibitors in the presence of mutated EGFR. We searched for additional target molecules involved in the action of the EGFR-tyrosine kinase inhibitor erlotinib in the absence of EGFR mutations, which might be suitable for combinatorial therapy approaches. MATERIALS AND METHODS: Erlotinib-resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 32 publications
2
11
0
Order By: Relevance
“…In contrast to lipid droplets, the Raman difference spectra revealed negative peaks for the membrane, cytoplasm, and nucleus on erlotinib treatment, implying that the Raman intensity of these components is increased in erlotinib-treated cells. This is perhaps due to an increase in the expression level of proteins during apoptosis on erlotinib treatment [ 68 , 69 , 76 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…In contrast to lipid droplets, the Raman difference spectra revealed negative peaks for the membrane, cytoplasm, and nucleus on erlotinib treatment, implying that the Raman intensity of these components is increased in erlotinib-treated cells. This is perhaps due to an increase in the expression level of proteins during apoptosis on erlotinib treatment [ 68 , 69 , 76 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…In the present study, we found that STO‐609 remains the same as IL‐6, and down‐regulation of IL‐8 is induced by HDM. Response to Tarceva and protein profiles in before and after treatment nonsmall cell lung cancer (NSCLC) models have suggested that AMPK is a putative target protein, while AMPK activation status impacts EGFR targeted drug response . No previous study has discussed the impact of EGFR‐TKI on AMPK pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Williams et al [ 8 ] demonstrated that the activation of CAMK (CAMK II and CAMK IV) inhibits cell cycle progression in small cell lung carcinoma (SCLC) cells. Furthermore, Hulsmann et al revealed that the activation of mitogen-activated protein kinase (MAPK) contributes to growth inhibition and apoptosis in human LC cells [ 9 ]. There is a wide consensus that CAMKK has been shown to undergo autophosphorylation and contains two isoforms (CAMKK1 and CAMKK2) [ 10 ].…”
Section: Introductionmentioning
confidence: 99%